Analisis Indeks Pencemar Kualitas Air Tukad Nyuling di Kabupaten Karangasem - I Kadek Ardi Putra; I Made Wahyu Wijaya (Jurnal Ecocentrism, 2021)
Tukad Nyuling is a watershed with a watershed area of 7,436 ha (BPDAS Undaanyar) and a length of 13 km, flowing year-round generally flowing to the south. Period I monitoring of BOD and detergent parameters in the upstream, middle and downstream of Tukad Nyuling has exceeded the class II water quality standard. Parametar total coliform in the downstream Tukad Nyuling condition has exceeded the standard of grade II water quality, with a concentration of 7,000/100 ml. COD parameters in the middle of Tukad Nyuling conditions that have exceeded the standard of class II water quality, where COD concentration reaches 31.10 mg/L. Monitoring period II BOD parameters in the upstream, middle and downstream Tukad Nyuling has exceeded the standard water quality class II, BOD concentration ranges from 5.28 mg/L to 5.79 mg/L. Concentrated detergent in the middle and downstream Tukad Nyuling has exceeded the standard of class II water quality, the concentration of detergent in the middle reaches 16.21 mg/L while in the downstream reaches 18.46 mg / L. Based on the status of water quality with the method of index pollutant upstream has a mild pollutant status while the middle and downstream have a moderate pollutant status.